How Does Antiretroviral Treatment Attenuate the Stigma of HIV? Evidence from a Cohort Study in Rural Uganda - Tsai, Alexander C.; Bangsberg, David R.; Bwana, Mwebesa; Haberer, Jessica E.; Frongillo, Edward A.; Muzoora, Conrad; Kumbakumba, Elias; Hunt, Peter W.; Martin, Jeffrey N.; Weiser, Sheri D. (AIDS and Behavior, 2013)
Program implementers and qualitative researchers have described how increasing availability of HIV antiretroviral therapy (ART) is associated with improvements in psychosocial health and internalized stigma. To determine whether, and through what channels, ART reduces internalized stigma, we analyzed data from 262 HIV-infected, treatment-naıve persons in rural Uganda followed from ART initiation over a median of 3.4 years. We fitted Poisson regression models with cluster-correlated robust estimates of variance, specifying internalized stigma as the dependent variable, adjusting for time on treatment as well as socio-demographic, clinical, and psychosocial variables. Over time on treatment, internalized stigma declined steadily, with the largest decline observed during the first 2 years of treatment. This trend remained statistically significant after multivariable adjustment (v2 = 28.3; P = 0.03), and appeared to be driven by ART-induced improvements in HIV symptom burden, physical and psychological wellbeing, and depression symptom severity
Keywords: Social stigma; Depression; Antiretroviral therapy; Highly active; HIV; Uganda